Hot paths and sectors of the energy metabolic process in the Jing-Jin-Ji urban agglomeration. (1st September 2022) - Xu, Dongxiao; Zhang, Yan; Yang, Zhifeng; Zheng, Hongmei; Wang, Xinjing
Abstract: China's Jing-Jin-Ji urban agglomeration shows exceptionally high urbanization and resource utilization problems that require to identify hot paths and sectors of energy metabolism, thus recognizing key links of cleaner production, and supporting energy conservation and emission reduction. In this paper, an energy metabolic network model was built for the urban agglomeration to simulate energy transfers between sectors using ecological network analysis, and path analysis was performed starting from initial production to identify critical paths and sectors. The chain of paths through 0–3 intermediate nodes dominated the energy metabolic processes, becoming the key to diagnosing problems. The critical paths in the urban agglomeration evolved from joint dominance by intra- and inter-city paths to inter-city paths, indicating increasingly coordinated development. Intra-city paths from Beijing's and Tianjin's Industry were always critical, whereas inter-city paths mainly started from Shijiazhuang's, Handan's, Tangshan's or Baoding's Industry; Beijing's, Tianjin's, Shijiazhuang's, Tangshan's and Handan's Industry played export roles, with Beijing's, Tianjin's, and Shijiazhuang's Industry also playing transfer roles and the other sectors (especially Construction) playing import roles. Above results will serve for the agglomeration's cleaner, more sustainable and more coordinated development. Graphical abstract: Image 1 Highlights: A sector-scale energy metabolic network of Jing-Ji-Ji urban agglomeration was developed. Path analysis was conducted to identify key paths and nodes. Paths with length ≤4 accounted for around 70% of the integrated metabolic intensity. Critical paths evolved from joint dominance by intra- and inter-city paths to inter-city paths. Industry sector often played export and transfer role, the other sectors played import roles.